Questions of perfection of quarantine phytosanitary control (supervision) on the customs border of the Eurasian Economic Union (Journal of actual problems of jurisprudence, 2019)
This article discusses the most pressing issues of legal support of phytosanitary control in countries belonging to the Eurasian Economic Union. A comprehensive analysis of legal acts in this area has been carried out. The ways of the legal solution of the issues of phytosanitary security at the customs border are considered, and their own vision and recommendations for the theoretical and practical improvementof phytosanitary security are proposed.The purpose of this study is to increase the effectiveness of quarantine phytosanitary control (supervision)at the customs border of the Eurasian Economic Union.The idea of the research is a legal analysis of the state of the legislation of the Republic of Kazakhstanin the field of phytosanitary security as the main factor of provision the food security of the country andthe population, the idea of the project is to scientifically substantiate the need to integrate the knowledgeand skills of state regulation accumulated in the world practice in the sphere under consideration. Alsothe idea of the project is to develop author’s proposals for the adoption of specialized legislation regulatinglegal relations in the sphere of phytosanitary security and improving the norms of the agricultural andother legislation of the Republic of Kazakhstan in this field.A retrospective analysis of the laws of quarantine phytosanitary control (supervision) at the customsborder, both in the countries of the Eurasian Economic Union, and the Republic of Kazakhstan was carriedout.The theoretical and methodological basis of the article is based on an organic combination of the requirementsof general scientific and private scientific methodology. In addition, private scientific methodswere used in the work: structural and system analysis, concrete historical, comparative legal, logical,statistical methods, etc.Key words: Phytosanitary security, phytosanitary control (supervision), the Eurasian EconomicUnion, customs regulation, customs border, the Republic of Kazakhstan, the Eurasian Economic Union,the laws of the CIS countries, the unified register of quarantine products, plant quarantine, agricultural